Raloxifene Protects Oxygen-glucose-deprived Astrocyte Cells Used To Mimic Hypoxic-ischemic Brain Injury - Toro Urrego, Nicolas (2024)
Background. Hypoxic-ischemic brain injury is one primary cause of long-term neurologicaldisability, morbidity, and death worldwide. The decrease in blood flow and oxygen concentration leads toinsufficient nutrient supply to the brain, energy depletion, increased free radical generation, and mitochondrialdysfunction. Perinatal asphyxia — the oxygen supply suspension near birth-time — causes hypoxic-ischemicbrain injury and is a major risk factor for neurodevelopmental damage. In pathological scenarios, raloxifene, aselective estrogen receptor modulator, has shown neuroprotective effects. Purpose. To examine whetherraloxifene showed neuroprotection in an oxygen-glucose deprivation/reoxygenation astrocyte cell model.Methods. T98G cells in culture were treated with a glucose-free DMEM medium and incubated at 37ºC in ahypoxia chamber with 1% O2 for 3, 6, 12, and 24 hours. Cultures were supplemented with raloxifene 1, 10, and100 nM during both glucose and oxygen deprivation and reoxygenation periods. Results. Raloxifene 100 nMand 10 nM improved cell survival — 65.34% and 70.56% — respectively compared to the control cell groups.Mitochondrial membrane potential was preserved by 58.9% 10 nM raloxifene and 81.57% 100 nM raloxifenecotreatment. Raloxifene cotreatment reduced superoxide production by 72.72% and peroxide production by57%. Mitochondrial mass was preserved by 47.4%, 75.5%, and 89% in T98G cells exposed to 6-hour oxygenglucosedeprivation followed by 3, 6, and 9 hours of reoxygenation, respectively. Conclusions. Raloxifeneimproved cell survival and mitochondrial membrane potential, and reduced lipid peroxidation and reactiveoxygen species (ROS) production, suggesting a direct effect on mitochondria. Raloxifene protected the oxygenglucose-deprived astrocyte cells used to mimic hypoxic-ischemic brain injury in this study.